Utilization of Annona muricata Leaf Extract as a Botanical Pesticide for Controlling Paracoccus marginatus of Acacia crassicarpa Nursery - Darlis, Viny Volcherina; Bakara, Jhon Pontas; Mardhiansyah, M.; Pebriandi (Journal of Tropical Silviculture, 2024)
Acacia crassicarpa is one of the Fabaceae family which has been widely recommended for planting in the context of rehabilitation of critical lands as well as HTI development, due to its fast growth, wide adaptation, and resistance to unfavorable conditions. Acacia crassicarpa in the nursery is often attacked by various pests, one of which is the Paracoccus marginatus. Efforts to the use of Annona muricata leaf control Paracoccus marginatus currently carried out generally use chemical methods. extract is an alternative that can be used as an environmentally friendly pesticide. This study aims to determine the utilization of Annona muricata leaf extract to control Paracoccus marginatus in Acacia crassicarpa nursery and to determine the best concentration of Annona muricata leaf extract for the mortality rate of Paracoccus marginatus. This study used a completely randomized design method (CRD) consisting of 4 treatments and 4 replications with concentrations of vegetable pesticide solutions. P0 = control (without Annona muricata leaf extract), P1 = 10 g/l of water, P2 = 20 g/l of water, P3 = 30 g/l of water. The results showed that the botanical pesticide from Annon muricata leaf extract concentration of 30 g/l of water is the best concentration in controlling Paracoccus marginatus with the fastest initial time of insect death is 2.5 hours (2 hours 30 minutes), 50% fastest time of death (LT50) is 8.5 hours (8 hours 30 minutes) and total mortality amounted to 90 %. Keywords: Annona muricata, Paracoccus marginatus, Acacia crassicarpa, Botanical Pesticide